Pengujian Impact Sambungan Circuseam Pada Pressure Vessel Dengan Pengelasan Multiproses Material SA 516 70N Melalui Production Test - Rakha Aditya Aji; Ari Wibowo (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
Pressure vessels are one of the important components needed in the petroleum sector. A pressure vessel is a vessel that has pressure because it is used to store fluids in the form of liquid or gas which has the characteristics of being resistant to high and low temperatures. The object of this research is a pressure vessel which is operated at a low temperature of -25°C. The pressure vessel is fabricated through multi process welding, namely GMAW (Gas Metal Arc Welding) on the root, SAW (Submerged Arc Welding) on the outside, and FCAW (Flux Cored Arc Welding) on the inside. One of the quality of the welding can be seen from impact testing. Impact testing was carried out on the weld metal and HAZ (Heat Affected Zone) areas in each welding process at -25oC which was preceded by the PWHT (Post Weld Heat Treatment) process. A pressure vessel is considered to comply the standard if the impact test results show the energy absorbed is above 27 Joules. The impact test results show that all test specimens absorb energy above 27 Joules so that they comply the standards for use as pressure vessels and the welding process used can be applied in the manufacture of pressure vessels.